Multitarget Activities of Kleeb Bua Daeng, a Thai Traditional Herbal Formula, Against Alzheimer's Disease - Chantha Chheng; Pornthip Waiwut; Kusawadee Plekratoke; Yaowared Chulikhit; Supawadee Daodee; Orawan Monthakantirat; Supaporn Pitiporn; Natdanai Musigavong; Pakakrong Kwankhao; Chantana Boonyarat (MDPI AG, 2020)
The Kleeb Bua Daeng formula (KBD) is a Thai traditional medicine for brain health promotion. On the basis of the activities of its individual components, the KBD could have good potential for the treatment of Alzheimer's disease (AD). Herein, we investigated the KBD as an AD treatment. The ethanol extracts of KBD and its components, i.e., Nelumbo nucifera (NN), Piper nigrum fruits (BP), and the aerial part of Centella asiatica (CA) exhibited antioxidant activity, as determined by both ABTS and DPPH assays. The Ellman's assay revealed that the KBD, NN, and BP showed an ability to inhibit acetylcholinesterase. The thioflavin T assay indicated that the KBD, NN, BP, and CA inhibited beta-amyloid aggregation. The neuroprotection and Western blot analysis revealed that the KBD reduced H2O2-induced neuronal cell death by inhibiting the expression of pro-apoptotic factors, i.e., cleaved caspase-9 and -3, p-P65, p-JNK, and p-GSK-3β, as well as by inducing expression of anti-apoptotic factors, i.e., MCl1, BClxl, and survivin. Furthermore, the KBD could improve scopolamine induced memory deficit in mice. Our results illustrate that the KBD with multimode action has the potential to be employed in AD treatment. Thus, the KBD could be used as an alternative novel choice for the prevention and treatment of patients with AD.